Marx's appreciation of James Steuart: A theory of history and value - William McColloch (The University of Utah, Department of Economics, 2011)
This paper argues that despite a growing body of scholarly literature on Sir James Steuart, his theory of history and influence on Marxian political economy has been largely ignored. The approach of this paper is motivated, in part, by Marx's sympathetic treatment of Steuart found in the opening of his Theories of Surplus Value, and in scattered asides throughout the remainder of his work. We argue that Steuart's importance to students of the history of political economy is three-fold: First, following Marx, we consider the unique and dynamic role played by history in Steuart's system. Steuart appears to have been the first thinker in political economy to both recognize the historical specificity of capitalism, and to conspicuously incorporate that realization into his system. Secondly, in Steuart's approach to the question of value and profit we find conceptions that defy easy classification. Steuart is seen to plainly abandon the mercantilist understanding of profit as determined in the sphere of exchange alone, and to treat what he calls the real value of a commodity as intimately related to its necessary labor time. Finally, we argue that Steuart's contemporary notoriety made him far more influential than is commonly recognized. In particular, we contend that Steuart, via Hegel, may have exercised an indirect influence on Marx's own theory of history, in ways that Marx could not have recognized.
Keywords: B12; B14; B41; N43; 330; History of Economic Thought; Sir James Steuart; Classical School